2018
DOI: 10.3823/2559
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hemodynamic responses to two different types of moderate physical exercise during pregnancy: a randomized clinical trial

Abstract: Background/Aim: Maternal hemodynamic responses (heart rate, systolic and diastolic blood pressure) were compared during two types of moderate-intensity physical exercise. Methods:A randomized clinical trial compared 120 pregnant women performing physical exercise on a treadmill (n=64) or stationary bicycle (n=56). In 44 of these women (n=23 treadmill; n=21 bicycle), blood pressure was monitored for 24 hours following exercise. Repeated-measures analysis compared maternal heart rate, systolic and diastolic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…One study comparing stationary cycling and treadmill walking found similar increases in SBP irrespective of the mode (bike: + 8 mmHg p = 0.06, treadmill: + 8 mmHg p = 0.02) and DBP (bike: + 5 mmHg p = 0.39, treadmill: + 6 mmHg p = 0.18). 51 Fieril et al 92 also reported an increase in SBP and DBP following 15 and 30 min of aerobic exercise (p = 0.01 and p = 0.001 respectively). These two studies, along with De Olivieria et al 91 found a post exercise hypotensive response, in which BP dropped below baseline levels from 50 min to 14 hours post exercise.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…One study comparing stationary cycling and treadmill walking found similar increases in SBP irrespective of the mode (bike: + 8 mmHg p = 0.06, treadmill: + 8 mmHg p = 0.02) and DBP (bike: + 5 mmHg p = 0.39, treadmill: + 6 mmHg p = 0.18). 51 Fieril et al 92 also reported an increase in SBP and DBP following 15 and 30 min of aerobic exercise (p = 0.01 and p = 0.001 respectively). These two studies, along with De Olivieria et al 91 found a post exercise hypotensive response, in which BP dropped below baseline levels from 50 min to 14 hours post exercise.…”
Section: Resultsmentioning
confidence: 92%
“…The risk of bias can be viewed in Supplementary file 2 (Tables S1–S5) . Overall, the risk of bias in the RCTs and randomized clinical trials was low, with 27 (71%) studies assessed as low risk, 20 , 34 , 36 39 , 41 , 42 , 51 69 10 (27%) studies classified as unclear 44 , 69 76 and one (2%) study considered high risk. 77 The cohort 78 84 and case control studies 85 90 were all classified as low (71%) to moderate (29%) risk of bias ( Tables S2 and S3 ), as were the two crossover studies ( Table S4 ).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations